International Spinal Cord Injury Pain (ISCIP) Classification: Part 2. Initial validation using vignettes - Bryce, Thomas N.; Treede, Rolf-Detlef (Spinal cord, 2012)
Study design: International validation study using self-administered surveys. Objectives: To investigate the utility and reliability of the International Spinal Cord Injury Pain (ISCIP) Classification as used by clinicians. Methods: Seventy-five clinical vignettes (case histories) were prepared by the members of the ISCIP Classification group and assigned to a category by consensus. Vignettes were incorporated into an Internet survey distributed to clinicians. Clinicians were asked, for each vignette, to decide on the number of pain components present and to classify each using the ISCIP Classification. Results: The average respondent had 86% of the questions on the number of pain components correct. The overall correctness in determining whether pain was nociceptive was 79%, whereas the correctness in determining whether pain was neuropathic was 77%. Correctness in determining if pain was musculoskeletal was 84%, whereas for visceral pain, neuropathic at-level spinal cord injury (SCI) and below-level SCI pain it was 85%, 57% and 73%, respectively. Using strict criteria, the overall correctness in determining pain type was 68% (versus an expected 95%), but with maximally relaxed criteria, it increased to 85%. Conclusions: The reliability of use of the ISCIP Classification by clinicians (who received minimal training in its use) using a clinical vignette approach is moderate. Some subtypes of pain proved challenging to classify. The ISCIP should be tested for reliability by applying it to real persons with pain after SCI. Based on the results of this validation process, the instructions accompanying the ISCIP Classification for classifying subtypes of pain have been clarified.